THE IMPORT ANCE OF PROFESSIONAL DEVELOPMENT ACTIVITIES TO ENHANCE EFL TEACHERS’ PROFESSIONAL DEVELOPMENT - Khulaifiyah, (JEE (Journal of English Education), 2017)
The article presents the idea of professional development activities from some views to enhance EFL teachers‟ quality and to meet the changing needs of the students which can be best implemented by EFL teachers. Some considerations about professional development activities to be reminder are 1) a match to existing teacher needs, 2) a match to existing school needs, 3) teacher involvment in the activities, 4) active participation opportunities, 5) long-term engangement and 6) high-quality instructors.The contribution will give EFL teachers views about continuous professional development reflect which upon pertinent common goals effectively. In sum up, the professional development activities for EFL teacherwill maintain a vital and critical role in the development of quality of teachers.